PEMETAAN DATA RUMAH TANGGA MISKIN NELAYAN TRADISIONAL DI WILAYAH KABUPATEN KERAWANG - Ummanah Ummanah; Ari Anggarani Winadi Prasetyoning Tyas; Nizirwan Anwar (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
This study aims to find a map of the causes of poverty according to poor households, explain the determinant factors that influence the behavior of poor households and the level of community welfare, formulate the main strategy of effective poverty reduction based on the causes of poverty, design an effective empowerment model in improving household welfare. poor households and identify strategic roles that can be carried out by the government, especially development instructors in implementing poverty reduction strategies. This research was conducted in the district of Karawang. This research is motivated by the existence of gaps that occur between layers of the population in a society, where every policy that emphasizes direct attacks on the causes of poverty is a problem from the government. Neo-Liberal theory basically says that an important component of a society is indiviual freedom. Poverty is the absence of effential assets and opportunities to which every human being is entitled. Everyone should have access to basic education and primary health care.Poverty is better measured by measured by measures: basic education, health care, nutrition, clean water and sanitation, in addition to income, employement, and wages. The types of data collected in this study are primary data and secondary data. This research was conducted through a series of procedures which included obtaining permits, compiling interview guidelines, determining informants, conducting field research, analyzing data, and preparing draft reports. The results of this study prove that fishing households optimize the role of family members in trying to overcome the problem of poverty, carry out a double income pattern by allocating their workforce to various types of work, facilitate diversification of fishing equipment in fishing communities, use productive organizations by actively participating in groups. social gatherings and recitation groups to help overcome the problem of poverty, the existence of social relations carried out by fishermen to maintain their existence